Tax morality and payment mechanisms associated with motor vehicle taxpayer compliance at samsat Surakarta - Dexa Novrian Siswantara; Mahameru Rosy Rochmatullah (Institute of Computer Science (IOCS), 2026)
This study examines the relationship between Tax Morality, Payment Mechanism, and motor vehicle taxpayer compliance at the Surakarta SAMSAT Office. The study addresses the limited examination of internal behavioral and external administrative factors simultaneously in the local motor vehicle taxation context. A quantitative approach with descriptive and associative designs was employed. The population consisted of 647,685 registered motor vehicle taxpayers in 2025, with 100 respondents selected using the Slovin formula with a 10% margin of error and accidental sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using IBM SPSS. The results show that Tax Morality has a significant negative relationship with taxpayer compliance (? = ?0.506; t = ?9.225; p < 0.001), while Payment Mechanism also has a significant negative relationship (? = ?0.767; t = ?13.981; p < 0.001). These negative relationships differ from the positive relationships generally expected theoretically. The regression model is jointly significant (F = 122.271; p < 0.001), with an R² of 0.716, indicating that Tax Morality and Payment Mechanism statistically account for 71.6% of the variation in taxpayer compliance. The findings contribute empirical evidence that internal moral orientation and external payment mechanisms do not necessarily have positive relationships with taxpayer compliance in the Surakarta SAMSAT context